Pemanfaatan Ikan Laut sebagai Sumber Nutrisi yang Bernilai Ekonomis bagi Warga Pesisir Pantai Nipah, Malaka, Kecamatan Pemenang, KLU - Rifana Cholidah, Ima Arum Lestarini, Ida Ayu Eka Widiastuti, Seto Priyambodo, Basuki Rahmat (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2018)
The territory of Indonesia consists of land and waters including the oceans, which constitute a large part of our beloved earth with an area of sea and land in Indonesia is 2/3 of the region in the form of oceans, while 1/3 of the area is land. However, the potential of the maritime sector has not been taken seriously, therefore the development and cultivation of the potential of marine resources need to be improved. The West Nusa Tenggara Province consists of 2 large islands, namely Lombok and Sumbawa and is surrounded by around 280 small islands. The total area of NTB province is 49,312.19 km2 consisting of land area of 20,153.15 km2 (40.87%) and sea waters covering 29,159.04 km2 (59.13%). The potential of marine resources as a source of nutrition for health is importantly known and understood by the community, especially those who live in coastal areas. Abundant marine resources in NTB province can also be processed into some foods which have economic values. However, knowledge of fishermen, housewife and coastal residents about the benefits of marine resources and how the processing the resources is still very low. This community service aims to provide information to residents who live around the coast about marine resources as essential nutrients for life and provide counseling and training on how to process marine resources into economically valuable food.